Memetic algorithms for reconstruction of binary images on triangular grids with 3 and 6 projections - Nagy, Benedek; Moisi, Elisa Valentina (Elsevier Science Bv, 2017)
When an image is given with only some measurable data, e.g., projections, the most important task is to reconstruct it, i.e., to find an image that provides the measured data. These tomographic problems are frequently used in the theory and applications of image processing. In this paper, memetic algorithms are investigated on triangular grids for the reconstruction of binary images using their three and six direction projections. The algorithm generates an initial population using the network flow algorithm for two of the input projections. The reconstructed images evolve towards an optimal solution or close to the optimal solution, by using crossover operators and guided mutation operators. The quality of the images is improved by using switching components and compactness operator. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Triangular grid; Image reconstruction; Memetic algorithm; Binary tomography; Genetic algorithm; Non-traditional grid